RETRACTED: Optimizing the organizational and economic mechanism for the efficient functioning of multifunctional centers in Russia - Nevalenova Ekaterina; Volkodavova Elena; Naugolnova Irina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001